PENGARUH TINGKAT KOMPETENSI DAN KOMUNIKASI TERHADAP PRODUKTIVITAS KERJAANGGOTA POLRI DI SUBDIT FASHARKAN DITPOLUDARAKORPOLAIRUD BAHARKAM POLRI - Gada Sembada; Muhammad Nurseha (Sekolah Tinggi Manajemen IMMI, 2019)
Increasing the ability of human resources needs to be implemented so that the work productivity of employees can always develop. Efforts to improve human resource capabilities carried out by Dit Poludara Korpolairud on Polri Members in the Fasharkan Sub-Directorate of Poludara Sub-Directorate Korpolairud Baharkam Polri, among others, were carried out through competency and interpersonal communication. Both of these efforts have been carried out, but still the employee’s work productivity still fluctuates.The aim to be achieved in this study was to determine the effect of the level of competency and interpersonal communication on the work productivity of the National Police Members in the Fasharkan Sub-Directorate of the Poludara Sub-directorate of Korpolairud Baharkam Polri.The study was conducted by taking the research population of the National Police Members in Fasharkan Dit Poludara Subdit Korpolairud Baharkam Polri, which amounted to 72 employees. The research data was obtained from a questionnaire given to 44 respondents who were taken by simple random sampling method.The results of the analysis obtained the conclusion that the level of competence and interpersonal communication has a positive influence on employee work productivity both partially and jointly.On the conclusions obtained, the efforts to increase work productivity should be done by improving the level of competence and interpersonal communication because the better the level of competence, the better the work productivity of employees, as well as the better the interpersonal communication, the better work productivity of employees.